Design and characterization of inhibitory peptides against Bleg1_2478, B3 subclass Metallo-β-lactamase - Selvaraju, Gayathri (2021)
Metallo β lactamase (MBL) is an enzyme which hydrolyses β lactam antibiotics. Their production by bacteria, particularly bacterial pathogens, is one of the mechanisms used to resist the action of the antibiotics. MBL requires zinc ions for this particular function. There are four classes of MBLs, B1, B2, B3 and B4 MBLs. Among them B3 MBLs do not have available clinical inhibitors and they have the widest substrate degradation spectrum. Previously, a hypothetical protein (HP) termed Bleg1_2478, which has a 3 D predicted structure and tested activity spectrum similar to B3 class MBL was discovered from Bacillus lehensis G1 alkaliphile. However, phylogenetic analysis showed that it is not related to any currently circulating B3 MBLs. As clinical inhibitors for B3 MBL are absent and that Bleg1_2478 is not related to any currently circulating B3 MBLs, there is a need to develop inhibitors specifically for Bleg1_2478. Therefore, this study aimed to design and characterise peptides as inhibitors against Bleg1_2478. Inhibitory peptides were designed by retrieving peptides from CAMPR3 database and subsequently derivated based on functional residues around Bleg1_2478 active site which contains the zinc binding site. The binding energies of the peptides were determined via fixed protein ligand docking using YASARA and AutoDock Vina software and compared with those of the preferred substrate, ampicillin. As a result, nine peptides with higher binding energies (>8.52 kcal/mol) towards the enzyme Bleg1_2478 were successfully designed. These peptides were then used for global protein ligand docking to investigate other possible binding sites on the protein other than its active site. Inhibitory assay of these peptides on purified Bleg1_2478 recombinant protein was performed at 1, 10 and 20 μM respectively. The inhibitory peptides, RSWPWH and SSWWDR, depicted approximately 50% of inhibition of Bleg1_2478 at concentrations as low as 0.90 μM and 0.50 μM respectively. Analysis of the peptide protein interaction via isothermal titration calorimetry (ITC) showed a 1.5 and 3 fold increase in the binding affinity of RSWPWH and SSWWDR respectively towards Bleg1_2478; as compared to ampicillin. More significant is the binding strength of these peptides whereby they exhibited a respective 34 to 68 fold increase compared to ampicillin. Similar to ampicillin, both of the inhibitory peptides bind to Bleg1_2478 at one binding site, as can be observed from their stoichiometric value. Physicochemical computation of both peptides revealed, the basic or cationic nature of RSWPWH and its predicted binding site near the vicinity of the active site of Bleg1_2478 may have contributed for to its ease of interaction with Bleg1_2478, hence, giving forth free energy (G) and enthalpy factor values that are more favourable and spontaneous. The dissociation constant, Kd, revealed that RSWPWH is more susceptible to dissociate from the protein due to the location of its binding site which expose it to pH changes caused by the cellular environment. On the other hand, SSWWDR inhibitory peptide is less prone to dissociate from the protein as it has zero net charge and it binds to the narrow groove of the Bleg1_2478 active site, an area that is less accessible and less susceptible to changes in the cellular environment. In conclusion, both peptides obtained can be used as a potential inhibitor against Bleg1_2478 and possibly other B3 MBLs.